The TLCC - CCL Merger and Union Policy and Impact on Wages - Chartier, Roger (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1957)
SummaryIn this article, the Author addresses himself to answering tentatively the following questions. What is the situation regarding the evolution of the wage structure, or relative wage rates, and the general level of money or real wages? To what extent can unionism be insolated as a causal factor in such movements, apart from traditional "market forces" or government action? In what ways, if at all, is the TLCC-CCL merger likely to bring about changes in the present wage situation?